Effect of Fobio on Intensity of Moler Disease (Fusarium oxysporum) on Various Shallot Cultivars - Elvira, Nolla Dwi; Wiyatiningsih, Sri; Suryaminarsih, Penta (CROPSAVER, 2023)
Fusarium oxysporum is the pathogen that causes moler disease which can reduce the productivity of shallot plants. The use of cultivars greatly affects the production. Control method that is more environmentally friendly is currently being pursued towards organic farming. Fobio is a biopesticide containing plant root microorganisms as biological control agents. This study aims to determine the effect of Fobio biopesticide on Fusarium wilt (moler) disease incidence and production of three shallot cultivars. The experiment was conducted in the shallot planting area of Sukorejo Village, Rejoso District, Nganjuk Regency, East Java. This experiment was arranged in the split plot design with two factors. The main plot of the concentration of the biopesticide formula (Fobio) consisted of 3 levels namely control (chemical fungicide), 5 ml/liter, and 10 ml/liter, and the subplot of shallot cultivar consisted of 3 types namely Tajuk, Biru Lanchor, and Super Philip. The observation in this study were the incubation period, disease symptoms, disease intensity, and shallot bulb yield. The results showed that Fobio biopesticide at the concentration of 10 ml/liter caused the same disease suppression as chemical fungicide (control) in the three shallot cultivars with the disease incidence of 18.78%. Fobio biopesticide concentration of 10 ml/liter had also the same effect as chemical fungicide on the production of those shallot cultivars, with the average wet weight of 2.25 kg/treatment and dry weight of 1.49 kg/treatment.